Assessing the bodily-kinesthetic intelligence of pre-schoolers - Michelaki, E.; Bournelli, P. (European Journal of Physical Education and Sport Science, 2022)
The study focused on the presentation of an instrument developed to assess bodily-kinesthetic intelligence of pre-schoolers. There are presented activities and their evaluative procedure for the assessment of bodily-kinesthetic intelligence of preschool children. A secondary aim of this study was to evaluate, with the use of this instrument, a creative dance intervention programme which focused on the development of pre-schoolers` bodily-kinesthetic intelligence. The sample of this study consisted of 28 preschool children in total, split into intervention and control groups. In the intervention group there were 15 preschool children (7 boys and 8 girls), with an average age of 5 ± 0.5 years, and in the control group 13 children (7 boys and 6 girls). To examine the effect of the creative dance intervention program on the development of children`s bodily-kinesthetic intelligence, data were analyzed with RM-ANOVA. By these means, we arrived at the conclusion that these creative dance sessions gave pre-school children the opportunity to employ and develop their bodily-kinesthetic intelligence.